1965
DOI: 10.1139/b65-084
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure in Detached, Senescing Wheat Leaves

Abstract: Detached leaves of Little Club wheat were allowed to senesce on water or on kinetin (10 mg/l.) in petri dishes on the laboratory bench. Samples taken at intervals of 24 to 48 hours for 8 to 10 days were fixed in permanganate or osmium tetroxide, embedded, usually in araldite or epon, and examined by electron microscopy. Abnormalities were noted in the endoplasmic reticulum (ER) of the mesophyll cells 2 days after the leaves were detached; ER and cytoplasmic ribosomes were not present after 4 or 5 days. Swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1
1

Year Published

1969
1969
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 13 publications
5
36
1
1
Order By: Relevance
“…A decrease in the proportion of polysomes during growth has been indicated in Chinese cabbage leaves (6) and maize shoots (10), and an electron microscope study revealed the presence of polysome-like clusters in aging cucumber cotyledons (5). An over-all loss of ribosomes during aging has been observed in several plant tissues both by electron microscopy (1, 4,5,13) and from biochemical studies (6,15) Preparation of Ribosomes and Polysomes. The leaves (10 to 40 g) were rapidly washed, blotted dry, and weighed; then they were cooled and ground by pestle and mortar with enough acid-washed sand to facilitate grinding and with one to two times their volume of tris-magnesium buffer containing 0.05 M tris, pH 7.8, and 0.01 M magnesium acetate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the proportion of polysomes during growth has been indicated in Chinese cabbage leaves (6) and maize shoots (10), and an electron microscope study revealed the presence of polysome-like clusters in aging cucumber cotyledons (5). An over-all loss of ribosomes during aging has been observed in several plant tissues both by electron microscopy (1, 4,5,13) and from biochemical studies (6,15) Preparation of Ribosomes and Polysomes. The leaves (10 to 40 g) were rapidly washed, blotted dry, and weighed; then they were cooled and ground by pestle and mortar with enough acid-washed sand to facilitate grinding and with one to two times their volume of tris-magnesium buffer containing 0.05 M tris, pH 7.8, and 0.01 M magnesium acetate.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the proportion of polysomes during growth has been indicated in Chinese cabbage leaves (6) and maize shoots (10), and an electron microscope study revealed the presence of polysome-like clusters in aging cucumber cotyledons (5). An over-all loss of ribosomes during aging has been observed in several plant tissues both by electron microscopy (1,4,5,13) and from biochemical studies (6,15) 16 hr of artificial light (about 1000 ft-c). The temperature varied between 15 to 25 C in winter and 20 to 35 C in summer.…”
mentioning
confidence: 96%
“…The bean cotyledon mitochondria were isolated on day 1, day 4, and day 7. Figure 7 shows that the swelling of mitochondria on day 1 and day 7 (24). Opik (21) also found that maximal activity of bean cotyledon mitochondria was from the cotyledons at the age of 36 hr after planting and then it gradually decreased.…”
Section: Materiais and Methodsmentioning
confidence: 88%
“…Many recent studies have demonstrated that several different factors such as mineral or vitamin deficiencies (7,18), treatment with unnatural pyrimidine (11,22), treatment with herbicides (2, 10), senescence (17), and genetic alternation (3,15,21) can cause similar aberrant ultrastructural changes in the chloroplast structure. It is evident from our results that 6706 also disrupts the chloroplast morphology and development.…”
Section: Discussionmentioning
confidence: 99%